White-collar attorney defence strategies: an empirical study of a national sample. (1st January 2014) - Gottschalk, Petter
Every year, an average of 100 white-collar criminals is sentenced to prison in Norway. Based on newspaper reports and court documents, a database of more than 300 convicted criminals is applied in this research to answer the following research question: What links can be found from attorney defence strategies (substance defence, symbolic defence, and information control) to crime case characteristics (persons involved, money amount, and prison sentence)? A number of statistically significant relationships were identified: 1) substance defence varies positively with symbolic defence, positively with money amount in crime, and negatively with number of persons involved in crime; 2) information control varies negatively with money amount in crime and negatively with number of persons involved in crime; 3) symbolic defence varies positively with substance defence, negatively with information control, and positively with money amount in crime